PENENTUAN SETTING LEVEL OPTIMAL UNTUK PEMBUATAN BRIKET BERBAHAN BAKU LIMBAH DAUN PENYULINGAN NILAM - Setyanto, Nasir Widha; Riawati, Lely; Lukodono, Rio Prasetyo; Ardianwilianri, Raditya (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2016)
Patchouli oil is the main ingredient of parfume as the binder of the fragrances. Patchouli oil is the distillates of patchouli’s leaves and stems. The distillation produces waste (dry leaves) which nowadays used as fertilizer, myrrh, mosquito coil, compost, and as the fuel of the distillation process itself. Up to today, the use of dry leaves as the distillation’s fuel is by burning them normally. We believe that this fuel can be used by other sectors by forming it as brickets. This research aims to find the right parameter combination of the patchouli’s dry leaves, stems, and other materials with taguchi’s method that hopefully can be used as household and even industrial fuels. Factors that contribute the most to elevates the average value of the combustion’s duration are the adhesive level, patchouli leaves’ carbon particle size, and drying duration. Whereas the combustion duration interval is 44,3036< Upredicted < 61,62.